Assessment of efficiency of subgingival irrigation with 10% povidone-iodine as an adjunct to mechanical treatment ( clinical and histological study ) - يوسف, تهامة; يوسف, باسمة; سليمان, رزان (Latakia University Journal -Medical Sciences Series, 2021)
Mechanical treatment aims to remove the germs that causes periodontal disease, but the complete elimination of these germs remains difficult. Therefore, most of the research was directed to developing methods to improve attempts to eliminate them, on top of which is the sharing of the drug solution with mechanical treatment. Aim of study: To evaluate the effectiveness of subgingival irrigation using 10% povidone-iodine as a supportive treatment to scaling and root planning (SRP), and to study its effectiveness on inflammatory lymphoid and plasma cells histological. Materials and Methods: the study was conducted on 20 jaw of ten patients with moderate chronic periodontitis. The Gi index was evaluated. 10 biopsies were taken. Each jaw was divided into right and left halves. One side was treated with scaling and root planning only, while the other side was treated with ( SRP with subgingival irrigation using 10% povidone-iodine). Clinical indicators and tissue samples were evaluated before work and during observation periods (one, three months). Results: subgingival irrigation with povidone-iodine 10% together with SRP showed a statistically significant reduction in GI index, with a statistically significant reduction in inflammatory lymphoid cells during (one, three months) posttreatment.